Leisure Studies and Spirituality: A Christian Critique - Paul Heintzman (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2010)
Conceptual discussions of leisure have often had spiritual overtones or linked leisure with spirituality. The links between the two concepts are becoming widely recognized and discussed in a wide range of leisure studies areas: therapeutic recreation, camping, recreational land management, outdoor recreation, tourism, and community recreation. Increasingly empirical research is being conducted on this relationship. Christians respond in a variety of ways to the increased social scientific interest in the relationship between leisure and spirituality: for some Christian spirituality is the only true spirituality; some compartmentalize or dichotomize spirituality; some believe non-Christians experience spirituality; some believe that spirituality reaches its fullest potential in relationship with God; and some see spirituality as a complex process. Positively, the renewed interest in spirituality may be seen as recognition of spiritual need and an opportunity for introducing Christian spirituality and the Christian spiritual tradition of leisure. However there are also areas of concern. First, there is a need to expand the “interiority” of contemporary discussions of leisure and spirituality and to emphasize transcendence. Second, contemporary discussions of leisure and spirituality often focus on the inner self with little discussion of relationships with others or of community. Third, there is a need to go beyond spiritual experience to spiritual well-being. Fourth, as the majority of theoretical reflection and empirical investigation on leisure and spirituality has focused on nature-based recreation and spirituality, more emphasis needs to be placed on all forms of leisure in all settings. Fifth, as the vast majority of studies on leisure and spirituality have been small scale qualitative studies, the adoption of various methods of studying and understanding the relationship between leisure and spirituality needs to be encouraged. Sixth, there is a need within the leisure studies field to make connections with the 20 centuries of Christian spirituality.
Keywords: Leisure; spirituality; recreation